Development of Huay Tako Temple Folk Museum Database Nakhon Pathom Province - Janarnu, Tara (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
The objective of this research was to develop a database. and disseminate information related to information resources within the Folk Museum, Huay Tako Temple, Nakhon Pathom Province. To be a source of research for the general public and those interested. The researcher has conducted research. Gather information related to the museum's work system. and analyze current operating conditions To study and analyze basic information Determine the scope of data that must be used in database design. To be suitable for the work system Create a database and information system It uses an open code database program that works through the website. To develop an online database and evaluate the satisfaction of users of the completed database to improve the database to be complete The development of the Huai Tako Temple Folk Museum database has been published through the website. and used a questionnaire to assess satisfaction with the use of the database. The evaluation results found that Satisfaction with database design The content of the database Data display aspect of the utilization of the database system and satisfaction with the database after use overall average score was 3.97, which was at a high level.